Neuronal TGF-β1 mediates IL-9/mast cell interaction and exacerbates excitotoxicity in newborn mice - Bettina Mesplès; Romain H. Fontaine; Vincent Lelièvre; Jean-Marie Launay; Pierre Gressens (Neurobiology of Disease, 2005)
Intraneocortical injection of ibotenate, a glutamate analog, in newborn mice produces damage mimicking lesions observed in human infants with cerebral palsy. Previous research using this model has demonstrated that pretreatment with IL-9, a Th2 cytokine, significantly exacerbated excitotoxic brain lesions. The goal of this study is to identify the underlying pathophysiological mechanism of lesion formation. Pretreatment with TGF-β1 produced the same effects as IL-9 on ibotenate-induced lesions. IL-9 effects were abolished when a specific TGF-β1 neutralizing antibody is administered at the same time. Real-time PCR, Western blot, and immunohistochemistry showed that pretreatment with IL-9 increased TGF-β1 neocortical expression. In vitro studies using real-time PCR and immunocytochemistry demonstrated that neurons were a major contributor in IL-9-induced increase of TGF-β1. In c-Kit mast cell-deficient mice, TGF-β1 failed to exacerbate excitotoxic brain lesions, suggesting a key role of mast cells in TGF-β1 effects. A specific inhibitor of mast cell degranulation and histamine receptor blockers abrogated TGF-β1 effects on excitotoxic lesions, providing further evidence of mast cell involvement and the role of mast cell-derived histamine. Finally, in vitro studies using a mast cell line showed that TGF-β1 increased histamine in the supernatant. In aggregate, these data support the notion that neuronal TGF-β1 plays a key role in the IL-9/mast cell interaction, which leads to an exacerbation of neonatal excitotoxic damage through an increased extracellular histamine concentration. The identification of this pathway, if confirmed in human neonates, might have important implications for understanding and preventing cerebral palsy.